Poverty eradication resilience and its influencing factors in key counties assisted by rural revitalization:An empirical study of Youyang Tujia and Miao Autonomous County - LIU Yuanli, YAO Yan, LIAO Heping (Ziyuan Kexue)
[Objective] Consolidating and expanding poverty alleviation achievements results is not only fundamental to effective rural revitalization, but also the path to common prosperity, for which poverty eradication resilience provides a new approach and perspective. [Methods] This study introduced the concept of resilience and analyzed the concept and connotation of “poverty eradication resilience”. We selected 77 administrative villages in Youyang Tujia and Miao Autonomous County as the study area, with 2023 serving as the assessment year, and explored the level of poverty eradication resilience and its influencing factors for rural revitalization key support counties by using the fully aligned polygonal composite graphical method and geographic detector. [Results] (1) Poverty eradication resilience emphasizes the endogenous development and self-renewal ability of the regional system, which is a specific manifestation of the development ability of the poverty-stricken areas, and can accurately reflect the current situation of consolidating poverty eradication results or outcomes. (2) The overall level of poverty eradication resilience in the study area is low, with obvious regional differences, characterized by a gourd-shaped distribution, that is, the number of higher level and lower level villages are in the upper and lower peak areas of the “gourd” respectively, and the ability to cope with various external risks is poor. (3) Industrial development is the endogenous driving force, capable cadres and money-making genius are the exogenous driving force, construction of digital villages is the demand driving force, and policy support is the guarantee driving force to enhancing the poverty eradication resilience. [Conclusion] By integrating of rural primary, secondary, and tertiary industries, the leading role of party members and cadres, village task forces and money-making genius, stimulating of the endogenous motivation of households out of poverty, and promoting the construction of smart villages, it can improve the level of poverty eradication resilience in key counties for rural revitalization, which is conducive to promote comprehensive rural revitalization.